The Effect of Financial Report Transparency and Accountability on Public Trust in Savings and Loan Units (USP) in Rupat District” - Saripah Anom; Rosmida Rosmida (Universitas KH. Abdul Chalim Mojokerto, 2025)
MSMEs as a support for the national economy need the support of microfinance institutions such as the Savings and Loan Unit (USP). However, in Rupat District, there are still problems of lack of transparency and weak accountability of USP management. This condition has an impact on declining member trust, so an empirical study is needed to see the influence of these two factors. This study aims to determine the influence of financial report transparency and accountability on public trust. The research method uses a quantitative approach by collecting data through the distribution of questionnaires to USP members. The research sample amounted to 72 respondents who were selected using saturated sampling techniques. Descriptive statistical results show that transparency, accountability, and public trust are in the high category. The validity and reliability test states that all research instruments are valid and reliable. The regression results showed that the transparency of financial statements had a positive and significant effect on public confidence (t = 4,016; Sig = 0.001), as well as accountability that had a significant effect (t = 4.623; sig = 0.001). The F test showed a significant simultaneous influence (Fcal = 83.865; Sig = 0.001) with an Adjusted R² of 0.700. Based on these findings, the study recommends that USP improve information disclosure, timeliness of reporting, and strengthen accountability mechanisms to maintain and strengthen public trust.